Der More Economic Approach in der Missbrauchsaufsicht: einige kritische Anmerkungen zu den Vorschlägen der Generaldirektion Wettbewerb - André Schmidt; Stefan Voigt (Georg-August-Universität Göttingen, Volkswirtschaftliches Seminar, 2006)
The Commission's proposals regarding the implementation of art. 82 TEC are shortly presented. The authors show that they can be interpreted as another step towards a more economic approach because their implementation would strengthen the rule of reason even further. The Commission's proposal to introduce an efficiency defense is critically discussed as are some of the other means proposed to deal with various behavioral strategies such as pricing, rebates, bundling, and aftermarkets.
Keywords: K21; L41; 330; Wettbewerbspolitik; Wettbewerbsaufsicht; Kritik; EU-Staaten